Cannibalizing the canon Dada techniques in East-Central Europe - Botar, Oliver A. I. 1957-; Denischenko, Irina; Dobó, Gábor 1987-; Szeredi, Merse Pál 1990- (Brill, 2024)
This rich, in-depth exploration of Dada’s roots in East-Central Europe is a vital addition to existing research on Dada and the avant-garde. Through deeply researched case studies and employing novel theoretical approaches, the volume rewrites the history of Dada as a story of cultural and political hybridity, border-crossings, transitions, and transgressions, across political, class and gender lines. Dismantling prevailing notions of Dada as a "Western" movement, the contributors to this volume present East-Central Europe as the locus of Dada activity and techniques. The articles explore how artists from the region pre-figured Dada as well as actively "cannibalized", that is, reabsorbed and further hybridized, a range of avant-garde techniques, thus challenging "Western" cultural hegemony.
Keywords: Dadaismus; Ostmitteleuropa; Aufsatzsammlung